Substance Abuse in Aging Population - Alireza Jazayeri; Nahaleh Moshtagh (University of Social Welfare & Rehabilitation Sciences, 2006)
substance abuse' specially opiates and prescribed drugs are spreading among the older adults. Most of the time it begins as an attempt to medicate chronic pains, medical conditions and loneliness. In other instances, it simply is the continuation of a problem that begun in young adulthood. But scholars and specialists in both fields of Addiction and Gerontology, rather neglected this fast growing problem, to the extent that we almost have no data on the epidemiology, prevention and treatment modalities among the substance abusing old adults in Iran. This paper reflects the necessity of designing age specific programs to identify and treat this group. Besides, some of the most effictive methods of treatment in other countries are reviewed.